2021
DOI: 10.3389/fgene.2021.701652
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Outcomes of 5′ Splice Site GT>GC Variants That Generate Wild-Type Transcripts Differ Significantly Between Full-Length and Minigene Splicing Assays

Abstract: Combining data derived from a meta-analysis of human disease-associated 5′ splice site GT>GC (i.e., +2T>C) variants and a cell culture-based full-length gene splicing assay (FLGSA) of forward engineered +2T>C substitutions, we recently estimated that ∼15–18% of +2T>C variants can generate up to 84% wild-type transcripts relative to their wild-type counterparts. Herein, we analyzed the splicing outcomes of 20 +2T>C variants that generate some wild-type transcripts in two minig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
2
10
0
Order By: Relevance
“…In accordance, a residual extent of correct splicing was further demonstrated by expression of the SBDS mutant minigenes, which also revealed, besides the exon 2 skipping event, the usage of a cryptic splice site which was not appreciable ex vivo likely because of the nonsense-mediated decay effect. Altogether, these data on the residual usage of the correct 5′ss, which has key pathophysiological implications for SDS, are in agreement with recent research showing that GT>GC variants at 5’ss can be compatible with correctly processed mRNA [ 30 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…In accordance, a residual extent of correct splicing was further demonstrated by expression of the SBDS mutant minigenes, which also revealed, besides the exon 2 skipping event, the usage of a cryptic splice site which was not appreciable ex vivo likely because of the nonsense-mediated decay effect. Altogether, these data on the residual usage of the correct 5′ss, which has key pathophysiological implications for SDS, are in agreement with recent research showing that GT>GC variants at 5’ss can be compatible with correctly processed mRNA [ 30 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 90%
“…Variants of c.2755A>T and c.2863A>T, predicted by BDGP and HSF to have a significant impact on ESE / ESS motifs, did not cause exon 24 skipping, and the WT minigene of exon 12 only produced the exon 12-excluded transcript. Coincidentally, the same results that candidate variants did not alter pre-mRNA splicing were revealed in other studies (Suarez-Artiles et al, 2018;Wang et al, 2020;Zhang et al, 2021) and there was a previous study that suggested only 18 of the 20 wild-type minigene constructs produced the desired wild-type transcripts in the pSPL3 context, improving the awareness of the limitations of minigene assays and emphasizing the importance of sequence context in regulating splicing (Lin et al, 2021). The reasons for these results may be related to the defects of software, the limited transferability of minigenes, the differential expression of splicing factors in cells, the interference of the mRNA secondary structure, etc.…”
Section: Discussionsupporting
confidence: 63%
“…For this reason, we used an in vitro minigene assay to characterize the effect of this synonymous variant on splicing. Although there is an inherent limitation to the minigene‐based analysis of splicing (Lin et al, 2021), our experiment successfully demonstrates the activation of a cryptic splice site with no leaky expression of the wild‐type transcript. This was used as supportive evidence in clarifying the clinical significance of this TECTA synonymous variant.…”
Section: Family‐individuala Hearing Loss Featuresb Genotypec Ethnicit...mentioning
confidence: 68%
“…For this reason, we used an in vitro minigene assay to characterize the effect of this synonymous variant on splicing. Although there is an inherent limitation to the minigene-based analysis of splicing (Lin et al, 2021) Our analysis thus strongly suggests this variant arose as a founder variant in Latinos of African ancestry, which explains why this variant is rare or absent in other subpopulations of gnomAD and our internal databases. Disease-relevant variants occurring at elevated frequencies due to bottleneck events in a population's history are expected to occur in the LAI data, and several studies have identified founder variants in genes associated with other diseases in the Latino ancestry (Gonzaga-Jauregui et al, 2015).…”
mentioning
confidence: 75%